Intimate partner violence in Nepal: Latent patterns and association with depressive symptoms. (December 2019) - Clark, Cari Jo; Cheong, Yuk Fai; Gupta, Jhumka; Ferguson, Gemma; Shrestha, Binita; Shrestha, Prabin Nanicha; Yount, Kathryn M.
Abstract: Existing data suggest that there are distinct patterns (or classes) of intimate partner violence (IPV) experience that depart from dichotomous categorizations used to monitor progress toward Sustainable Development Goal 5.2. Less is known about the patterning of IPV in non-Western settings. This study estimates distinct classes of IPV experience in Nepal and examines potential community-level variability in these classes and in the association between IPV class and depressive symptoms. This study used data collected in 2016 from a random sample of Nepalese married women of reproductive age (N = 1440) living in 72 communities in three districts (Nawalparasi, Chitwan, and Kapilvastu). We used fixed effects and random effects latent class models of 2 through 6 classes. We fit a negative binomial regression model adjusted for relevant confounders to examine the relationship of the latent IPV classes with depressive symptoms. A four-class model was the best fitting. It included a "low exposure" class (77.36% of the sample) characterized by a low probability of experiencing any form of IPV, a "sexual violence" class (9.03% of the sample) characterized by a high probability of experiencing a form of sexual violence, a "moderate violence" class (6.60% of the sample) characterized by modest probabilities of experiencing less severe emotional and physical IPV, and a "systematic violence" class (7.01% of the sample) characterized by a high probability of being exposed to all forms of IPV. Adding random effects did not improve model fit, suggesting no community-level variations in classes. Relative to membership in the low exposure class, membership in all other classes was associated with a higher count of depressive symptoms. Those in the systematic class had a mean weighted symptom count 2.29 times that of the low exposure group. Classes of IPV exposure must be identified to ensure that surveillance and programming are attuned to women's experiences of violence. Highlights: First quantitative examination of classes in women's experience of IPV in Nepal. First multilevel LCA to identify common classes of IPV across communities. Classes of experience corroborate those found in other settings. Classes of experience are different from the way that IPV is monitored globally.